2018
DOI: 10.1017/dsj.2018.14
|View full text |Cite
|
Sign up to set email alerts
|

Identifying challenges in crowdfunded product development: a review of Kickstarter projects

Abstract: This paper provides an empirical review of the reward-based crowdfunding platform Kickstarter.com, with the aim to explore and identify challenges in crowdfunded product development, which consequently can lead to failure of the crowdfunding campaign. The review was based on the analysis of a total of 144 successfully funded ‘technology’ campaigns, which all concerned the creation of physical consumer hardware preordered by campaign backers. The analysis was built around a failure mode model, which was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…Thus, the lack of consideration for production methods in the previous development cycle lead to the several redesigns. Design for manufacturing is considered to be one of the main challenges faced by hardware startups [36], and our analysis show that it was also the case for PeeFence, as they had to scale their production significantly in each cycle. Recent studies that investigate the negative consequences of additive manufacturing make similar conclusions [34,35].…”
Section: The Freedom Of 3d Printing Can Lead To Altered Solution Desimentioning
confidence: 97%
“…Thus, the lack of consideration for production methods in the previous development cycle lead to the several redesigns. Design for manufacturing is considered to be one of the main challenges faced by hardware startups [36], and our analysis show that it was also the case for PeeFence, as they had to scale their production significantly in each cycle. Recent studies that investigate the negative consequences of additive manufacturing make similar conclusions [34,35].…”
Section: The Freedom Of 3d Printing Can Lead To Altered Solution Desimentioning
confidence: 97%
“…The rapid growth of crowdfunding has boosted academic research and related legislation such as the Jumpstart Our Business Startups Act (JOBS) [23]. Primary research interests include the descriptive study of the crowdfunding phenomenon [3], [24], the taxonomy of crowdfunding processes [6], [12], policy facilitating crowdfunding [8], [25], prediction of crowdfunding success [15] and sources of delays or cancellations of successfully crowdfunded product development [2], and applications of crowdfunding campaigns to entrepreneurship education [4]. Specifically, prediction-oriented studies have suggested that social networks [13], [26] and campaign qualities [14], [27] play essential roles in crowdfunding success.…”
Section: How Crowdfunding Work For Design Innovationmentioning
confidence: 99%
“…The RWW framework had been used by many established companies such as 3M and General Electric to evaluate internal innovation projects for go/kill decisions [35] and later modified to evaluate technology startups for accelerator selection [36]. In particular, the RWW framework allows one to evaluate a wide spectrum of product, market, team, risk, and strategic factors of an innovation project by answering guiding questions in three main aspects [2]:…”
Section: B Predictors Of Crowdfunding Successmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the review, the ability of campaign starters to make promises about product features and the project features created in this context plays an important role in the success of the project. The study also shows how crowdfunding platforms can be used in research with both data libraries and product development cases (Jensen & Özkil, 2018). The research conducted by Qianzhou and his team focuses mainly on the main points of the projects such as category and target.…”
Section: Related Workmentioning
confidence: 99%